(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the research of creation and activities of the organs of press of left and left centrist parties of Ukraine. The author, analyzing the history of such newspapers as “Tovarish” (SPU), “Kommunist” (KPU), “Nasha gazeta” (SDPU(o)), claims that precisely through these publications one can see the real face of the political parties. The dynamics of circulation, geography of spreading and language of the publications, all point to different tendencies in activities of SPU, KPU, SDPU(o).